My Italian secret [videorecording (DVD)] : the forgotten heroes of the Holocaust - Jacoby, Oren; Rossellini, Isabella; Loggia, Robert ([Publisher not identified], 2015)
Tells the untold story of Tour de France cycling champion Gino Bartali and other courageous Italians who risked their lives to rescue Jews, partisans and other refugees in Nazi-occupied Italy.